Multi-Objective EV Charging and Comfort Management Considering V2G Functionality and Distribution System Constraints - Turkoglu, Aligul Selim; Guldorum, Hilmi Cihan; Erdinc, Ozan (IEEE, 2023)
Planning electric vehicle (EV) charging management has become a significant issue as the percentage of EVs on the road rises. The adverse effects of EVs on the distribution system (DS) can be mitigated by carefully managing their charging. In addition, the vehicle-to-grid (V2G) service enables EVs to supply energy when the power system needs it. In this study, the proposed multi-objective optimization model, which is developed in the form of mixed-integer quadratically constrained programming (MIQCP), examines the comfort of EVs participating in the grid ancillary services in an EV parking lot (EVPL) concept and the cost of the EVPL operator simultaneously. Moreover, the effect of the proposed model on the important variables of the DS, such as power flow, voltage, and line losses, is examined. The developed model is evaluated using the IEEE 33-bus test system with four different case studies and a 15-minute time resolution. Thanks to the multi-objective approach, the results demonstrate that the comfort of EVs during ancillary services can be raised by taking the cost of charging and comfort violation into account jointly.
Keywords: Ancillary services; comfort violation; distribution system; electric vehicle; optimal power flow; Computer Science; Energy & Fuels